Barriers to fruit and vegetable consumption among farmers' market incentive programme users in Illinois, USA. Issue 7 (19th February 2018) - Singleton, Chelsea R; Fouché, Sydney; Deshpande, Rucha; Odoms-Young, Angela; Chatman, Corey; Spreen, Connie
Abstract: Objective: Previous research indicates that low-income individuals often struggle to consume the recommended amount of fruits and vegetables (F&V). LINK Up Illinois is a farmers' market incentive programme that aims to increase F&V consumption among Supplemental Nutrition Assistance Program (SNAP) recipients by improving access to and affordability of locally grown foods. The present research aimed to identify barriers to F&V consumption that exist among users of the LINK Up Illinois programme. Design: Cross-sectional. Setting: Farmers' markets in Chicago, Springfield, Northbrook, Woodstock, Aurora and Urbana, IL. Subjects: In 2016, a volunteer sample of 140 LINK Up Illinois users (mean age 42·5 years; 81·7 % female; 28·7 % African American; 44·0 % obese) completed a survey at participating farmers' markets across the state. Information on demographics, food shopping behaviours, programme satisfaction, barriers to F&V consumption and frequency of F&V consumption was collected and examined. Results: Approximately 23 % of survey participants reported consuming F&V ≥3 times/d. The barriers to F&V consumption most often reported by survey participants were the cost of F&V (29·5 %), spoilage (18·6 %), knowing how to cook F&V (8·7 %) and not thinking about F&V when hungry (8·6 %). Results from multivariable-adjusted logistic regression models suggested that reporting one or more barriers was associated with reduced odds of consuming vegetables ≥3 times/d, but not fruits. Conclusions: Cost, spoilage and knowledge of cooking are key barriers to F&V consumption that exist among LINK Up Illinois users. Strategies are needed to mitigate these barriers and increase F&V consumption in this population.